Staffing and Job Stress on Motivation of Employees in Al Ihsan General Hospital - Ina Ratnamiasih; Putra Mochamad Lazwar (TRIKONOMIKA, 2015)
Motivation has a very important role for the employees of the hospital in order to provide excellent service to the community. The importance of motivation, one of which is associated with the appropriate placement of human resources. This is done with the hope if the employee works in the right place and at the right position, then job motivation will increase. Based on the hypothesis, motivation of employee influenced job stress and heavy work environment can have an impact on employee stress. This research was conducted at Al Ihsan Hospital with a population of 75 employees. The data were obtained using a questionnaire and interview techniques. Data analysis is using structural equation modeling with the help of PLS analysis tools. The results showed that staffing and job stress have a significant effect on job motivation.